(untitled) (Research, Society and Development, 2021)
Contact athletes are often subject to orofacial trauma, especially in combat sports such as judo. However, the use of mouthguards can minimize the occurrence of trauma and prevent orofacial injuries resulting from sports. The objective of this work was to determine the prevalence of orofacial injuries in the athletes of the basic teams of the Brazilian judo team, as well as to evaluate their level of knowledge about the use of mouth protectors. A structured questionnaire was applied, with 10 specific questions for 46 athletes from the basic judo teams, male and female in Brazil, referring to the research theme. The results suggest that most athletes have already suffered some type of orofacial trauma during the practice of judo and most athletes do not use mouthguards, due to several factors. It is concluded that orofacial traumas showed a high prevalence, with lacerations of the lip, tongue and cheek mucosa being the most reported by judo athletes of the Brazilian team and their level of knowledge about the use of mouthguards was low, pointing to the need for informational actions on this subject among athletes of the Brazilian judo team.